TINJAUAN YURIDIS TINDAK PIDANA MENERIMA GRATIFIKASI BERDASARKAN UNDANG-UNDANG NOMOR 31 TAHUN 1999 JO UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Nadya Syafira; Erdianto Effendi; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
One form of corruption most widely disclosed at this time is corruption in the form ofgratification. Gratuity is a gift, reward or gift by a person who had received services or benefits orby persons who have or are dealing with a public or government agencies in the example to get acontract. The purpose of this thesis to determine criminal acts setting gratification as one ofcorruption in accordance with the value of living in Indonesia and to find out about the role of lawideal in setting gratification in Indonesia. This research is a normative legal research because it isdone by examining the library materials or secondary data on the crime of judicial reviewremuneration pursuant to Act No. 31 of 1999 Jo Act No. 20 of 2001. Source of data used primarylegal materials, secondary and tertiary. From the results of this study concluded, setting the crimeof graft as one of corruption in accordance with the value of life in Indonesia, that gratification isessentially not a crime. Because gratuities not be separated from the habits of society that havebeen entrenched. If a civil servant or state officials to immediately report the receipt of gratuities tothe Corruption Eradication Commission no later than 30 (thirty) days from the date of receipt ofgratuities, the criminal becomes clear. The ideal role of law in regulating graft in Indonesia, thatgratuities are expressed as corruption since the setting in the Act Eradication of Corruption ActNumber. 20 in 2001, however, must be based on the will of the people, the appropriate legalconsciousness of the people but it can be accepted by the community with full awareness.Keywords: Crime Receiving Gratuities